Guitarra davidconryi Ekins & Erpenbeck & Goudie & Hooper 2020, sp. nov. - Ekins, Merrick; Erpenbeck, Dirk; Goudie, Lisa; Hooper, John N. A. (Zenodo, 2020)
Guitarra davidconryi sp. nov. Figure 8, Table 4 urn:lsid:zoobank.org:act: E17354FE-8DB8-4821-AD2C-BEF8A5FD5A63 Material Examined : Holotype SAMA S2161, Commonwealth Marine Reserve, Great Australian Bight, South Australia, SZ 12, 35 o 40’ 46” S 135 o 41’ 37” E, 137 m, Smith-McIntyre grab, Coll. CSIRO on RV Investigator , Cruise IN 2017_C01, sample IN2017_C01_ SMG_212b, 24 April 2017. Etymology : This species is named for Mr David Mark Conry AM, outgoing Chair of the Board of the Queensland Museum and Co-Founder of Youngcare, in recognition of his guidance, great support, and generosity of his time during some challenging periods. Distribution : This species is presently known only from a single specimen from the Great Australian Bight, epipelagic depth. Description : Growth form : The holotype is composed of two small fragments, the largest is a small tear dropshaped fragment only 5 mm in length (Fig. 8 A), presumably from a much larger body, of which the remainder is unknown. All of the fragments of the holotype are now mounted on the SEM stubs and microscope slides. Colour : Off-white after preservation in ethanol. Ectosomal skeleton : The ectosome consists of a disorganised array of anisoxeote styles tangential to the surface, with occasional placochelae also distributed on the surface. Endosomal skeleton : The endosomal skeleton consists of widely spaced bundles of oxeas meeting the ectosome at an obtuse angle. Here the mesohyl contains the acanthoisochelae microscleres. Megascleres: Oxeas slightly curved with greatest thickness at the centre of the spicule, tapering to abrupt points (102–(139)–194 x 1.5–(3.8)– 5.3 µm, n=62). Very thin long sinuous styles slightly curved approximately one-third of their length towards the basal end, base tapering, slightly rounded, almost anisoxeote, points long and tapering (226–(310)–360 x 1.4–(3.9)–6.0 µm, n=41). Microscleres : Placochelae (26.5–(37.7)–48.6 x 8.1–(13.4)– 19.8 µm, n=34). Palmate acanthoisochelae (6.4– (10.5)–14.3 x 0.4–(0.8)– 1.4 µm, n=47). Molecular data: Due to the size of the small sample all of the material was used in the manufacture of microscope slides and SEM stubs. Remarks : Guitarra davidconryi sp. nov. is the first record of the genus from the Australian Exclusive Economic Zone (EEZ). The new species is most similar to G. indica Dendy, 1916 from shallow subtidal depths of Poshetra, India, in the morphology of its anisoxeote styles (which Dendy terms ‘tornostrongyles’), but differs in its gross morphology (massive versus cushion-shaped), and the possession of oxeas in addition to styles as megascleres. Dendy’s illustration of placochelae (Dendy 1916, Pl. I, Fig. 5b) depicts both mature and juvenile forms, with the latter referred to as developmental stages, but which are more likely to be palmate acanthoisochelae, similar to those in G. davidconryi sp. nov. , G. laplani Boury-Esnault et al. , 1993, G. sepia Lerner et al ., 2004, and G. solorzanoi Cristobo, 1998. To some extent this new species also resembles the brief description of G. novaezealandiae Dendy, 1924 from epipelagic depths in New Zealand, in its morphology, size of oxeas and placochelae, but differs from the latter in having styles as well as oxeas as structural megascleres, palmate acanthoisochelae and lacking sigmas. This species also bears some resemblance to G. exoclavata (Lévi, 1993) from mesophotic depths off New Caledonia, which is cushion shaped, has oxeas and exotyles as megascleres (both of which are magnitudes of size larger than the equivalent megascleres of G. davidconryi sp. nov. ), two sizes of placochelae, and tiny bipocilla-like isochelae. Guitarra bipocillifera Brøndsted, 1924 also from New Zealand epipelagic depths, synonymised with G. fimbriata Carter, 1874 by Bergquist & Fromont (1998) but an action not universally accepted by subsequent authors (e.g. Carballo …continued on the next page & Uriz 1998, Van Soest et al. 2018), has one type of spiny bipocilla-like isochelae similar to the palmate acanthoisochelae of G. davidconryi sp. nov. but lacks styles and has larger placochelae. A comparison of morphological characters found in all currently known species of Guitarra is presented in Table 4. : Published as part of Ekins, Merrick, Erpenbeck, Dirk, Goudie, Lisa & Hooper, John N. A., 2020, New carnivorous sponges and allied species from the Great Australian Bight, pp. 240-266 in Zootaxa 4878 (2) on pages 255-258, DOI: 10.11646/zootaxa.4878.2.2, http://zenodo.org/record/4424977 : {"references": ["Dendy, A. (1916) Report on the non-Calcareous Sponges collected by Mr. James Hornell at Okhamandal in Kattiawar in 1905 - 6. Report to the Government of Baroda on the Marine Zoology of Okhamandal in Kattiawar, 2, 93 - 146, pls. I-IV.", "Boury-Esnault, N., Pansini, M. & Uriz, M. J. (1993) Cosmopolitism in sponges: The ' complex' Guitarra fimbriata with description of a new species of Guitarra from the northeast Atlantic. In: Uriz, M. - J. & Rutzler, K. (Eds.), Recent Advances in Ecology and Systematics of Sponges. Scientia Marina, 57 (4), pp. 367 - 373.", "Lerner, C., Hajdu, E., Custodio, M. R. & van Soest, R. W. M. (2004) Guitarra sepia n. sp. from the Southwestern Atlantic (Demospongiae, Poecilosclerida, Guitarridae). First record of a Guitarra without placochelae. In: Pansini, M., Pronzato, R., Bavestrello, G., Manconi, R. & Sara, M. (Eds.), Sponge Science in the New Millenium. Bollettino dei Musei e degli Istituti Biologici dell'Universita di Genova, 68, pp. 405 - 411.", "Cristobo, F. J. (1998) Guitarra solorzanoi (Porifera, Demospongiae) a new species from the Galician coast (Northeast Atlantic). Ophelia, 48 (1), 25 - 34. https: // doi. org / 10.1080 / 00785236.1998.10428675", "Dendy, A. (1924) Porifera. Part I. Non-Antarctic sponges. Natural History Report. British Antarctic (Terra Nova) Expedition, 1910, Zoology, 6 (3), 269 - 392, pls. I-XV.", "Levi, C. (1993) Porifera Demospongiae: Spongiaires bathyaux de Nouvelle-Caledonie, recoltes par le ' Jean Charcot' Campagne BIOCAL, 1985. In: Crosnier, A. (Ed.), Resultats des Campagnes MUSORSTOM. Vol. 11. Memoires du Museum national de l'Histoire naturelle, (A), 158, pp. 9 - 87.", "Brondsted, H. V. (1924) Papers from Dr. Th. Mortensen's Pacific Expedition 1914 - 16. XXIII. Sponges from New Zealand. Part I. Videnskabelige Meddelelser fra Dansk naturhistorisk Forening i KjObenhavn, 77, 435 - 483.", "Carter, H. J. (1874) Descriptions and Figures of Deep-sea Sponges and their Spicules from the Atlantic Ocean, dredged up on board H. M. S. ' Porcupine', chiefly in 1869; with Figures and Descriptions of some remarkable Spicules from the Agulhas Shoal and Colon, Panama. Annals and Magazine of Natural History, Series 4, 14 (79), 207 - 221, 245 - 257, pls. XIII-XV. https: // doi. org / 10.1080 / 00222937408680964", "Lee, W. (1987) Guitarra abbotti and G. isabellae, new sponges from the eastern Pacific. Proceedings of the Biological Society of Washington, 100 (3), 465 - 479.", "Hentschel, E. (1914) Monaxone Kieselschwamme und Hornschwamme der Deutschen Sudpolar-Expedition 1901 - 1903. Deutsche Sudpolar-Expedition, 15 (1), 35 - 141, pls. IV-VIII.", "Topsent, E. (1916) Diagnoses d'eponges recueillies dans l'Antarctique par le Pourquoi-Pas? Bulletin du Museum national d'histoire naturelle, Paris, Series 1, 22 (3), 163 - 172.", "Van Soest, R. W. M, Boury-Esnault, N., Hooper, J. N. A., Rutzler, K., de Voogd, N. J., Alvarez, B., Hajdu, E., Pisera, A. B., Manconi, R., Schonberg, C., Klautau, M., Picton, B., Kelly, M., Vacelet, J., Dohrmann, M., Diaz, M. - C., Cardenas, P., Carballo, J. L., Rios, P. & Downey, R. (2018) World Porifera Database. Available from: http: // www. marinespecies. org / porifera / porifera. php (accessed 2 May 2020)"]}